Immunity, major depression, and panic disorder comorbidity - Andreoli, Antonio; Keller, Steven E.; Rabaeus, Maya; Zaugg, Line; Garrone, Gaston; Taban, Charles (Biological psychiatry (1969), 1992)
Because recent research reports indicated clinical and biological differences in major depression with and without comorbid Diagnostic and Statistical Manual of Mental Disorders (DSM-III-R) panic disorder, and as altered immune measures were reported in selected subgroups of depressive patients, we investigated 51 pairs of major depressive episode (MDE) subjects, and gender- and age-matched healthy controls in order to determine if T lymphocytes number and function abnormalities were associated with Panic Disorder comorbidity. We found that those MDE subjects with DSM-III-R panic disorder (PD) had greater numbers of T cells ( p < 0.05) and PHA mitogen ( p < 0.05) responses than depressive patients without PD, as well as increased phytohemagglutinin (PHA) ( p < 0.05) concanavalin A (ConA) ( p < 0.02) mitogen responses compared to their controls. These data suggest that panic disorder comorbidity significantly contributes to the variance of immunologic parameters in major depression and has to be carefully assessed within psychoimmunological studies of psychiatric patients with affective disorders.